Shape optimization of labyrinth seals - Aboula?ch, Rajae; Azelmat, Karim; Baranger, Jacques; Souissp, Ali (Zielona Góra: Uniwersytet Zielonogórski)
In this work, we determine the optimal shape of a labyrinth seal in a hydraulic Francis turbine. The numerical approximation of the optimal shape is obtained using shape optimization techniques. The flow is governed by Navier-Stokes equations. We first prove the existence of an optimal domain, and later we present the computation of the shape gradient which allows us to approximate numerically the optimal domain.
Keywords: shape optimization; hydraulic turbine; Navier-Stokes equations; Finite Element Method (FEM)